Faktor-Faktor yang Mempengaruhi Perkembangan Kota Banjarbaru - Suryansyah, Muhammad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
M. suryansyah, (2018), “Factors Affecting Banjarbaru City Development”This thesis writing under the guidance of Dr. H. Ahmad Yunani, SE, M.SiThis research was undertaken to (1) the influence of the number of industries,the number of transport, the number of housing on the development of Banjarbarutogether. (2) which influences the most dominant influence on the development ofBanjarbaru City.This research was conducted in Kota Banjarbaru using 10-year time series datausing multiple linear regression analysis.The results of this study indicate that the number of industries, the number oftransport, and the number of homes affect together on the development of BanjarbaruCity by conducting f. The most dominant factor influencing the growth of BanjarbaruCity individually is the number of transport. This is evidenced by a t-test that shows theprobability of a vehicle <0.05.